Shall we kill or enslave Caesar? Analyzing the Caesar model - Guillermina Jasso (Institute for the Study of Labor (IZA), 2008)
When a society overthrows a ruler - call the ruler Caesar - what determines whether Caesar is killed or enslaved? This paper presents a model of killing versus enslaving Caesar, based on a new theory which unifies justice, status, and power. The model pertains to societies which value ordinal goods like bravery, yielding predictions for three of the five types of societies - justice-nonmaterialistic, status, and power-nonmaterialistic. Results cover members' gains, effects of own rank and group size, and relative gains from killing or enslaving Caesar. Further results suggest that Caesar will be killed only in a justice-nonmaterialistic society, and from the noblest of motives - to achieve equal gains for members.
urn:nbn:de:101:1-20080421171
Keywords: D6; 330; Civil strife; coup d'état; regicide; tyrannicide; assassination; imprisonment; exile; sociobehavioral theory; justice; comparison; status; power; identity; happiness; personal qualitative characteristics; hierarchy; equality; Politische Unruhen; Public Choice; Soziale Werte; Gerechtigkeit; Postmaterialismus; Theorie